Clinical Psychological Figures in Healthcare Professionals: Resilience and Maladjustment as the “Cost of Care” - Merlo, Emanuele Maria; Stoian, Anca Pantea; Motofei, Ion G.; Settineri, Salvatore (Frontiers in Psychology, 2020)
Background: The health professionals are involved in the paths of care for patients with different medical conditions. Their life is frequently characterized by psychopathological outcomes so that it is possible to identify consistent burdens. Besides the possibility to develop pathological outcomes, some protective factors as resilience play a fundamental role in facilitating the adaptation process and the management of maladaptive patterns. Personal characteristics and specific indexes such as burdens and resilience are essential variables useful to study in-depth ongoing conditions and possible interventions. The study was aimed at highlighting the presence and the relations among factors as personal variables, burdens and resilience, to understand health professionals' specific structure and functions. Methods: The observation group was composed of 210 participants, 55 males (26,2%), and 155 females (73,8%), aged from 18 and 30 years old with an average of 25,92 years (SD = 3,33). The study considered personal characteristics of the subjects, such as age, gender, years of study, days of work per week, hours of work per week, years of work. Our study had been conducted with the use of measures related to burdens (Caregivers Burden Inventory) and resilience (Resilience Scale for Adults). Results: The performed analyses consisted of descriptive statistics, correlations and regressions among the considered variables. Several significant correlations emerged among personal characteristics, CBI and RSA variables. Specifically, age and work commitment indexes appeared to be significantly related to the development of burdens, differently from the years of study. Significant correlations emerged among personal and RSA variables, indicating precise directions for both domains. Age and gender were identified as predictors to perform multivariate regression analyses concerning CBI factors. Significant dependence relations emerged with reference to all CBI variables. Conclusion: Pathological outcomes and resilience factors represent two sides of the health professionals' experiences, also known as "invisible patients". Greater knowledge about present conditions and future possibilities is a well-known need in literature so that the current analyses considered fundamental factors. In line with state of the art, future studies are needed in order to deepen elusive phenomena underlying maladjustment.